AWE-10 An international survey on the diagnosis and management of severe gastrointestinal dysmotility. (June 2019) - Vasant, Dipesh H; Pironi, Loris; Bozzetti, Frederico; Cuerda, Cristina; Joly, Francisca; Kelly, Darlene; Paine, Peter; Staun, Michael; Szczepanek, Kinga; Gossum, André Van; Wanten, Geert; Lal, Simon
Abstract : Introduction: Severe gastrointestinal dysmotility (GID) can be sub-classified into Chronic Intestinal Pseudo-obstruction (CIPO) and Enteric Dysmotility (ED) subtypes. We surveyed current opinions on the diagnosis and management of GID amongst experts from different countries. Methods: An survey questionnaire developed by the European society for Clinical Nutrition and Metabolism (ESPEN) was circulated electronically to members of ESPEN, European Society of Neurogastroenterology and Motility, and United European Gastroenterology. Only participants that completed all required components were included in the analysis. Results: Of 154 included participants, 82% were European, the majority were attending clinicians/professors (85%), based at either national/regional referral centres and/or academic institutions (87%). Almost all (93%) agreed that CIPO and ED should be classed separately. Most (73%), reported increased incidence of GID, with 69% reporting an increase in ED. GID associated with hypermobile Ehlers-Danlos Syndrome was the group with the largest increase in referrals (37%), however this trend was driven by observations from UK participants only (P<0.0001). Almost all clinicians (95%) find diagnosing GID difficult, with 57% finding ED more challenging and 32% find both types equally difficult. GID diagnosis is often delayed (CIPO: by >5 years according to 16%; ED: by >5 years according to 19%). Moreover, by the time of diagnosis, >10% of patients have had inappropriate operations according to 82% of clinicians. Small Bowel Manometry, a test mandated to diagnose ED, is surprisingly never used by 44%, and is only used in >50% cases by 21%. Full thickness biopsies are usually requested from planned/previous resections (33%) or when the diagnosis is unclear (43%), but seldom change medical treatment (12%), nutritional management (16%) and prognosis (25%). Very few treatments are useful for >50% of patients, with antibiotics for SIBO, prucalopride, and psychology felt to be the most useful. Parenteral Nutrition (PN) rarely leads to improvement in symptoms (28%), and is associated with PN dependency at 5-years according to the majority (56%). Conclusion: These data highlight the difficulties with diagnosing and managing GID, even in 'expert' hands, and inform the urgent need for international, multidisciplinary, clinical practice guidelines.